A Change in Time: American Journalism's 2013 Transition to a Commercial Publisher. - Friedman, Barbara G.; Forde, Kathy Roberts (American Journalism, 2023)
Change is never easy, especially for historians who have their feet firmly planted in the past. So, in 2013, when American Journalism editor Barbara G. Friedman and associate editor Kathy Roberts Forde proposed moving from independent university presses to a commercial academic publisher, there was apprehension. But theirs was a utilitarian goal: creating a solid path for journalism and mass communication scholars to achieve tenure and promotion at their universities in an age when metrics matter and expanding the journal's reach. In this reflection, part of American Journalism's fortieth anniversary essay series, the former editors explain how the transition from independent to commercial publishing enabled a "gem of a journal" to achieve—and exceed—those initial goals. The authors also offer some considerations for the future.